Triple Transition Ecosystem As Catalyst of Public Value Generation - Symeonidis, Dimitrios; Nikiforova, Anastasija (Conference on Digital Government Research, 2025)
Digital transformation is increasingly reshaping the public and private sectors by enhancing the efficiency and quality of services. With the integration of emerging technologies such as Artificial Intelligence (AI), blockchain, and Internet of Things (IoT), this transformation is becoming a key driver in achieving the United Nations Sustainable Development Goals (SDGs). This shift has given birth to concept of the “triple transition” emphasizes the interconnected the social, green and digital transitions as part of a systemic approach to achieve the SDGs. However, for these technologies to generate meaningful public value, they must rely on high-quality, accessible, and interoperable data. Public Data Ecosystems (PDEs) , as networks of stakeholders engaging in data exchange across the data lifecycle, provide a foundation for transparency and accountability as elements of public value. Their capacity to create broader societal and economic value remains limited without the synergy of advanced digital technologies. To this end, this study proposes the concept of Triple Transition Ecosystems (TTEs) networks of actors leveraging both PDEs and the four-intelligence (4I) paradigm (Data, Artificial, Collective, and Embodied Intelligence) to generate multidimensional public value aligned with the SDGs. Using a systematic literature review that includes thematic analysis informed by public value frameworks, we examine the potential of TTEs across various policy domains. Our findings indicate that TTEs have the potential to generate public value in terms of better service quality and governance, but also higher societal value. By conceptualizing TTEs, this study offers a novel framework for understanding digital transformation as a systemic enabler of sustainable development and provides actionable insights for researchers and policymakers seeking to design triple transition–oriented policies.